2020
DOI: 10.1038/s41598-020-60399-3
|View full text |Cite
|
Sign up to set email alerts
|

Subtypes of anterior circulation large artery occlusions with acute brain ischemic stroke

Abstract: Anterior circulation large artery occlusion (Ac-LAo) related acute ischemic stroke (AiS) is particularly common in clinics in China. We retrospectively analyzed 787 consecutively hospitalized AIS patients with AC-LAO in Hebei Province, China. AC-LAO was defined as a complete occlusion of at least one intracranial internal carotid artery (icA) or middle cerebral artery (McA) based on computed tomography or magnetic resonance angiography. Among eight subtypes of Ac-LAo, unilateral McA occlusion is the most commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
3
4
0
Order By: Relevance
“…LAA-type anterior circulation infarction is affected by a combination of genetic and environmental factors, and there are many studies on its pathogenesis and pathological process, but research on the contributors of LAA-type anterior circulation infarction is not conclusive. In the present study, consistent with the results of previous studies (11,12), the possible risk factors for the formation of LAAtype anterior circulation infarction were being male (62.7%), hypertension (60%), a history of stroke (46.7%), a NIHSS score of 5-15 (40%), an ASPECT score >7 (40%), diabetes mellitus (38.7%), a history of smoking (33.3%), a mRS score with a mean value in the moderate to high range, a relatively high percentage of these above risk factors, and mean values of serumtotalcholesterol (TC), glutamic acid (GLU), Uric acid(UA), and D-dipolymer (D-Di) higher than normal. In relation to the effects of TC, GLU, UA, D-Di, hypertension, diabetes, and smoking on blood vessels, research has shown that (13) TC abnormalities lead to vascular endothelial cell damage, which in turn induces vascular inflammatory responses, promotes foam cell formation and thus TC is involved in atherosclerosis by promoting the formation of foam cells.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…LAA-type anterior circulation infarction is affected by a combination of genetic and environmental factors, and there are many studies on its pathogenesis and pathological process, but research on the contributors of LAA-type anterior circulation infarction is not conclusive. In the present study, consistent with the results of previous studies (11,12), the possible risk factors for the formation of LAAtype anterior circulation infarction were being male (62.7%), hypertension (60%), a history of stroke (46.7%), a NIHSS score of 5-15 (40%), an ASPECT score >7 (40%), diabetes mellitus (38.7%), a history of smoking (33.3%), a mRS score with a mean value in the moderate to high range, a relatively high percentage of these above risk factors, and mean values of serumtotalcholesterol (TC), glutamic acid (GLU), Uric acid(UA), and D-dipolymer (D-Di) higher than normal. In relation to the effects of TC, GLU, UA, D-Di, hypertension, diabetes, and smoking on blood vessels, research has shown that (13) TC abnormalities lead to vascular endothelial cell damage, which in turn induces vascular inflammatory responses, promotes foam cell formation and thus TC is involved in atherosclerosis by promoting the formation of foam cells.…”
Section: Discussionsupporting
confidence: 94%
“…of the LAA type. Consistent with the findings of Zhang and others (12,18), the NIHSS score is an independent predictor of adverse clinical outcomes in patients with LAA anterior circulation infarction, and most patients with LAA anterior circulation infarction have large vessel stenosis, and due to stenosis and hypoperfusion, platelet clots, and fibrin accumulate in the arterial wall, leading to thrombosis. In addition high stroke-related scores are more likely to lead to large vessel occlusion, which in turn aggravates clinical symptoms.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, we found that stroke severity at admission was greater in the multiple AC-LAO patients than in unilateral MCA occlusion or unilateral ICA occlusion patients. This is consistent with a previously published study of patients with AC-LVO AIS, which showed that high NIHSS was associated with multiple AC-LAO (28).…”
Section: Discussionsupporting
confidence: 93%
“…[14][15][16][17][18] The most common sites of anterior circulation occlusion are unilateral middle cerebral artery (MCA) (49.8%), unilateral internal carotid artery (ICA) (24.1%) and tandem ICA/MCA (12.7%);. 19 In the posterior circulation most occlusive events occurred in the vertebral arteries followed by the basilar artery and posterior cerebral artery. 20 Paramedic assessment will be the first opportunity for large vessel occlusion (LVO) to be suspected and for patients to be triaged to a site capable of diagnosing and treating LVO with endovascular thrombectomy.…”
Section: Introductionmentioning
confidence: 99%